Local spin excitations in the rectangular ferromagnetic - Tanriverdiyev, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
A Green function analysis is used to study spin-waves excitations in a ferromagnetic semiconductor nanowires.The expressions of Green function for different spins of ferromagnetic nanowires are derived. The nanowireis modeled as having a cubic cross section. The results are illustrated numerically for a particular choice ofparameters.